Choking under pressure: the neuropsychological mechanisms of incentive-induced performance decrements - Yu, Rongjun (Frontiers in Behavioral Neuroscience, 2015)
In contrast to the assumption of efficiency wage models, which state that wage incentives should be positively correlated with productivity, high incentives may produce performance decrements in real life scenarios. Such a “choking under pressure” phenomenon exemplifies how psychological stress can profoundly shape human behavior, for good or for bad. Previous theories suggest that individual choking under pressure because that high pressure may distract individuals’ attention away from the task (the distraction account), raise the attention paid to step-by-step skill processes (the explicit monitoring account), or elevate the arousal in general (the over-arousal account). Recent neuroimaging studies have shown that several brain regions implicated in motivation and top-down control of attention also play a key role in stress-induced choking, supporting for the over-arousal and distraction theories of choking. This review aims to identify psychological factors that determine choking and the neural underpinnings of these processes. Insights into how incentives influence performance may aid engineering training regimens and interventions that equip individuals to better handle high-stakes-induced psychological stress, and to thrive under stress.